EKSPROPRIASI PEMEGANG SAHAM MINORITAS DALAM KEPEMILIKAN ULTIMAT PENGARUH PEMISAHAN HAK ALIRAN KAS DENGAN HAK KONTROL TERHADAP NILAI PERUSAHAAN - Djayanto, Johan; Lindrawati, Lindrawati; Tedjasuksmana, Budianto (Widya Mandala Surabaya Catholic University, 2013)
Concentrated ownership embedded in publicly-owned companies’ organizational structure could trigger the expropriation of mi-nority shareholders. Such expropriation happens when the control rights are bigger than the cash flow rights held. Separation between the two could be approached using a number of ownership mechanisms, such as pyramid ownership and cross-holding. Based on the concept of ultimate ownership, the objectives are to examine and analyse (1) the impacts of cash flow rights and control rights on the firm value, and (2) the extent to which the involvements of controlling shareholders in top management and the presence of second controlling shareholders as moderate variables influence the phenomena explained. The research design is quantitative. The target research population is Indonesian publicly-owned companies listed in the Indonesian Stock Exchange between the years 2007-2011. Samples are collected using purposive sampling technique accumulating to 1,895 observations with a 10% cut-off point on the control rights. Statistical evaluation are done through multiple regression tool. It was found that the controlling shareholders’ cash flow rights positively affect firm value, whilst control rights do not have any significant impact. The involvements of controlling shareholders in top management as moderate variable could amplify the negative effect of cash flow right leverage towards firm value, whereas calibration of those effect with the presence of second controlling shareholders as moderate variable does not yield significant results as was firstly hypothesized.